Pengaruh Motivasi Kerja, Lingkungan Kerja, Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Bagian Produksi PT Karya Mina Putra Divisi Kayu Kota Rembang - Qulub, Ahmad Thoriqqoiful; Ilhami, Susanti Dwi (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The goal of this study is to demonstrate how work motivation, work environment, and work discipline impact the productivity of employees at PT Karya Mina Putra's wood division in the city of Rembang. The study included employees from the wood section of PT Karya Mina Putra's production department in Rembang city. Utilizing questionnaires for data collection methods. The sampling technique employed was cluster sampling, which falls under the probability sampling category. Various data analysis techniques are applied through the utilization of multiple linear regression analysis. The study results indicate that Work Motivation (X1) has a small positive impact on employee work productivity, Work Environment (X2) shows a slight negative influence on employee work productivity, while Work Discipline (X3) significantly boosts employee work productivity. Based on the determination test results, it was found that the variables of training, career development, and work experience account for 51. 4% of the variance in employee productivity. The remaining 49. 6% is attributable to factors outside the scope of this particular analysis. keywords: Work Motivation, Work Environment, Work Discipline, and Work Productivity